Aggressive Clinical Deterioration of Recurrent Extramammary Paget’s Disease: A Case Report - Sewon Lee; Sang Yoon Kim; Heejin Bang; Kyoung Eun Lee (The Ewha Medical Journal)
Extramammary Paget’s Disease (EMPD) is a rare intraepithelial malignancy of apocrine bearing glands, which occur usually in the perianal region, vulva, scrotum, penis and ax-illa. Most of the disease are treated by surgical resection and the prognosis is generally good. Even though recurrent disease, it is usually slowly progressed with good prognosis. Here we describe the case of a 70-year-old male who has presented with initially just as an EMPD component of squamous cell carcinoma in inguinal skin, but he showed recur-rence of EMPD. The disease has progressed rapidly, finally he died of that EMPD in 2 months of recurrence. The purpose of this study is to report the rare case of fulminant disease course of EMPD after recurrence.